A funny thing happened on the way to the White House : [compact disc, unabridged] : humor, blunders, and other oddities from the presidential campaign trail - Osgood, Charles (Tantor Audio, 2008)
Osgood gathers amusing stories from politicians throughout American history. Stories about Harry Truman, Bob Dole, Barry Goldwater, and George W. Bush among many others will have listeners in stitches.